2011
DOI: 10.5902/223658343832
|View full text |Cite
|
Sign up to set email alerts
|

<b> Editorial - Revista Saúde</b>

Abstract: Nothing in science has any value to society if it is not communicated, and scientists are beginning to learn their social obligations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…[34] Mainly focusing on experimentals, Rohatgi et al suggested a mathematical model that can predict many characteristic properties such as the peak stress, the plateau stress, the densification strain, and the composite density of ceramic hollow sphere filled MMSFs subjected to free (unconstrained) compression. [51,53] The results proved excellent agreement to the experimental data gathered from the literature. [52] The compressive strength can be calculated by Equation 6.…”
Section: Compressive Strengthsupporting
confidence: 81%
See 1 more Smart Citation
“…[34] Mainly focusing on experimentals, Rohatgi et al suggested a mathematical model that can predict many characteristic properties such as the peak stress, the plateau stress, the densification strain, and the composite density of ceramic hollow sphere filled MMSFs subjected to free (unconstrained) compression. [51,53] The results proved excellent agreement to the experimental data gathered from the literature. [52] The compressive strength can be calculated by Equation 6.…”
Section: Compressive Strengthsupporting
confidence: 81%
“…[35] The filler material (or reinforcement in the composite technologist point of view) is usually built up from oxide ceramics or from iron based metals (steels). [3,6,13,36,37] In the group of ceramics, most commonly 'fly-ash' [22,[38][39][40][41][42][43][44][45][46][47][48][49] (in some cases surface treated fly-ash [29] ), alumina, [50][51][52][53][54] or silicon carbide [4,[52][53][54] are applied. Fly-ash is a byproduct of coal power plants, they are quite cheap and available in large quantities, however their chemical composition can significantly vary and the scatter in their diameter is relatively high.…”
Section: Introductionmentioning
confidence: 99%